1988
DOI: 10.1002/1097-0142(19880101)61:1<203::aid-cncr2820610134>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the upper aerodigestive tract.A case comparison analysis

Abstract: Although the etiologic importance of tobacco in risk of upper aerodigestive malignancies is unques-tioned, quantification of subsite-specific risks is less well delineated. Risk estimates from this case-control study are derived from self-administered comprehensive risk factor questionnaires distributed to newly registered patients at The University of Texas M.D. Anderson Hospital and Tumor Institute, Houston. Cases included 185 white patients with histologically confirmed squamous cell carcinoma of the upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
5

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 17 publications
5
42
0
5
Order By: Relevance
“…Since the etiology of a majority of HNSCC is associated with environmental exposure to chemical agents, e.g. tobacco and alcohol, 89,90 animal models of chemical carcinogenesis, compared with transplantation models, may more accurately reflect the clinical course of human disease. 5 Indeed, several studies have shown that both alcohol and tobacco act as cocarcinogens in a commonly employed model of chemical carcinogenesis.…”
mentioning
confidence: 99%
“…Since the etiology of a majority of HNSCC is associated with environmental exposure to chemical agents, e.g. tobacco and alcohol, 89,90 animal models of chemical carcinogenesis, compared with transplantation models, may more accurately reflect the clinical course of human disease. 5 Indeed, several studies have shown that both alcohol and tobacco act as cocarcinogens in a commonly employed model of chemical carcinogenesis.…”
mentioning
confidence: 99%
“…Over 90% of all head and neck cancers are observed to be squamous cell carcinomas [1,13]. The incidence of head and neck cancer increases with age; most patients being older than age 50 [3].…”
Section: Resultsmentioning
confidence: 99%
“…Other major HNCs include skin and salivary gland tumors including parotid tumors, skin malignancies, basal cell carcinoma, etc. The incidence of HNC increases with age; most patients being older than age 50 [3].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Spitz et al (1988) in Texas, United States, also showed a linear increase in risk with increasing packyears of cigarette smoking (P trend < 0.01 for both males and females). In males, the OR rose from 1.8 (95% CI 0.7, 4.4) for those who smoked 1.24 pack-years to 7.5 (95% CI 3.7, 15.3) for those who smoked >49 pack-years when compared with non-smokers.…”
Section: Tobacco Smokingmentioning
confidence: 87%